Analysis of Qualifications, Grades, and Work Experience of Quality Control Employees in the GMF Aeroasia Line Maintenance Division - Sudirman, Farhan Kamil; Siladjaja, Muljanto (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the role of qualifications, grades, and work experience in determining the performance of Quality Control (QC) employees in the Line Maintenance section of GMF AeroAsia. The method used is a qualitative approach with in-depth interview and observation techniques. The results of the study indicate that the three factors interact with each other and form a synergy that is very important in maintaining the quality and safety of aircraft maintenance operations. Qualifications provide the knowledge base needed to carry out tasks, grades affect the level of responsibility and decision-making ability, while work experience accelerates employees' adaptability in dealing with various situations. This study also reveals that in order to improve employee performance, companies need to strengthen training and career development programs, so that employees can continue to develop their technical and managerial skills. Overall, these findings contribute to human resource management at GMF AeroAsia and show that the synergy between qualifications, grades, and work experience is very important in improving quality and safety in Line Maintenance operations.